PREVALENCE OF NYCTOTHERUS AND BALANTIDIUM IN DIFFERENT ANURAN AMPHIBIANS OF AURANGABAD - SHAIKH, T.T.; NIKAM, S.R.; JADHAV, R.N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
During the present study two species of ciliates from different anuran amphibians were encountered in a period of one year (June 2003-May 2004), about 355 frogs were examined output of which 254 were found to be positive for ciliate infection, the percentage of incidence was 71.54%.